Hawaii Coastal Seawater CO2 Network: A Statistical Evaluation of a Decade of Observations on Tropical Coral Reefs - Terlouw, Gerianne J.; Knor, Lucie A. C. M.; De Carlo, Eric Heinen; Drupp, Patrick S.; Mackenzie, Fred T.; Li, Yuan Hui; Sutton, Adrienne J.; Plueddemann, Albert J.; Sabine, Christopher L. (Frontiers in Marine Science, 2019)
A statistical evaluation of nearly 10 years of high-resolution surface seawater carbon dioxide partial pressure (pCO2) time-series data collected from coastal moorings around O’ahu, Hawai’i suggest that these coral reef ecosystems were largely a net source of CO2 to the atmosphere between 2008 and 2016. The largest air-sea flux (1.24 ± 0.33 mol m−2 yr−1) and the largest variability in seawater pCO2 (950 μatm overall range or 8x the open ocean range) were observed at the CRIMP-2 site, near a shallow barrier coral reef system in Kaneohe Bay O’ahu. Two south shore sites, Kilo Nalu and Ala Wai, also exhibited about twice the surface water pCO2 variability of the open ocean, but had net fluxes that were much closer to the open ocean than the strongly calcifying system at CRIMP-2. All mooring sites showed the opposite seasonal cycle from the atmosphere, with the highest values in the summer and lower values in the winter. Average coastal diurnal variabilities ranged from a high of 192 μatm/day to a low of 32 μatm/day at the CRIMP-2 and Kilo Nalu sites, respectively, which is one to two orders of magnitude greater than observed at the open ocean site. Here we examine the modes and drivers of variability at the different coastal sites. Although daily to seasonal variations in pCO2 and air-sea CO2 fluxes are strongly affected by localized processes, basin-scale climate oscillations also affect the variability on interannual time scales.